Implementasi Penilaian Portofolio Dalam Pembelajaran Matematika Berbasis Lesson Study Di SMP Muhammadiyah Mojolaban Tahun Ajaran 2016/ 2017 - Happy, Foriwan Kika; , Dr. Sumardi, M.Si (2017)
The purpose of this study to determine: (1) understanding the teacher at SMP Muhammadiyah Mojolaban toward authentic assessment one portfolio assessment, (2) the implementation process assessment portfolio in mathematical learning -based lesson study,(3) the constraints in the implementation of the implementation of portfolio assessment in mathematics - based lesson study, This qualitative descriptive study carried on in SMP Muhammadiyah Mojolaban with research subjects are students of class VII B amounting to 24tudents. Data collection techniques used include erviews,observation, testing, evaluation, FGD and documentation. Data analysis techniques used in the study of data reduction, data presentation and conclusion. The results showed: (1) teacher at SMP Muhammadiyah Mojolaban not understand clearly about authentic assessment, one portfolio sessment. (2) The implementation of portfolio assessment in math learning lesson study based on the rise in the average value of math students and attitudes of students in the school for the better over time. (3) Constraints faced in the mentation of portfolio assessment in mathematics learning lesson based study is: (1) For the teacher: the difficulties in the application portfolio assessment as unfamiliar and too many aspects in value so that the difficulty in regulating the assessment. (2) For Students: students are not familiar with using the learning portfolio assessment, so many students are still confused; many students are not interested and less enthusiasm when learning are even rowdy it self: on a portfolio assessment, a lot of questions or tests that must be done so that many students who are lazy to work.